2016
DOI: 10.1186/s13046-016-0403-2
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based identification of genes associated with cancer progression and prognosis in hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths. The average survival and 5-year survival rates of HCC patients still remains poor. Thus, there is an urgent need to better understand the mechanisms of cancer progression in HCC and to identify useful biomarkers to predict prognosis.MethodsPublic data portals including Oncomine, The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) profiles were used to retrieve the HCC-related microarrays and to identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…A total of 522 patient samples with LUAD were retrieved from a cohort of TCGA database, while only 516 samples with mRNA expression value were available to analyze the association of gene expression with clinical characteristics. The gene expression level was categorized as high or low based on the median value referring to a previous study (Yin et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 522 patient samples with LUAD were retrieved from a cohort of TCGA database, while only 516 samples with mRNA expression value were available to analyze the association of gene expression with clinical characteristics. The gene expression level was categorized as high or low based on the median value referring to a previous study (Yin et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies used these public databases as powerful evidence to screen and identify novel biomarkers for diagnosis and prognosis. For instance, by retrieving data from Oncomine and TCGA, Yin et al () successfully identified a group of genes related to cancer progression and prognosis in hepatocellular carcinoma. Liu et al () identified six genes that may be potential therapeutic targets and biomarkers for diagnosis and prognosis in ovarian cancer, based on data retrieved from Oncomine, GEO, and TCGA.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Wang et al provided a pipeline for the identification of prognostic signatures for HCC OS prediction[5]. Microarray technology has since been applied to the study of genetic changes in HCC, has defined several different genetic variants of the disease, and has identified genetic features that predict poor outcomes and metastasis [6–8]. Although the cellular and molecular genetic alterations of HCC have been more well-understood through these technologies, the molecular mechanisms have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In current study, CLEC4G , GDF5 , CLEC1B , CLEC4M and FCN2 are among LCN-5-RNA signature that can classify cancer and normal tissue sample with high precision. Earlier, CLEC4M and GDF5 have been recognized as differentially expressed gene in various other cancers [68-70], while CLEC4G, CLEC1B and FCN2 were identified as genes that associated with cancer progression and prognosis in hepatocellular carcinoma [64, 7173]. Overall this analysis emphasizes the role of these signature genes in oncogenesis.…”
Section: Conclusion and Discussionmentioning
confidence: 67%